TESTING of ANTIBACTERIAL ACTIVITY of EXTRACTS of SEA CUCUMBER (Holothuria atra) against BACTERIA Pseudomonas aeruginosa - Adlita Eska Putri; Mery Sukmiwati; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research aims to know the sea cucumber Holothuria atra bioactive compounds and antibacterial activity of sea cucumber Holothuria atra extract against bacteria Pseudomonas aeruginosa. The methods used in this research is descriptive method i.e. extraction with methanol, test of phytochemicals, fractionation with a solution of butanol, hexane and ethyl acetate, and test the antibacterial activity against Pseudomonas aeruginosa bacteria using diffusion method with concentrations of 50%, 75% and 100%. The data obtained are presented in the form of tables and images. Results showed extracts of methanol the sea cucumber Holothuria atra detected compounds containing bioactive i.e. component steroids or Terpenoids, alkaloids, saponins and phenolic. The test results and the antibacterial activity the extracts of methanol the sea cucumber Holothuria atra against bacteria Pseudomonas aeruginosa diameter inhibition of bacteria ranged from 8,61 to 12,25mm and of three types of fractions used hexane fraction has a more dominant antibacterial potency with diameter inhibition of bacteria ranged from 13,46 to 14,63mm. Based on the results of research that the methanol extract of sea cucumber Holothuria atra has potential as an antibacterial. Keywords: Antibacterial, Extracts, Bioactive Components, Faction